A polyvalent DNA prime with matched polyvalent protein/GLA-SE boost regimen elicited the most robust and broad IgG and IgG3 V1V2 binding antibody and CD4+ T cell responses among 13 HIV vaccine trials - Zoe Moodie; Shuying Sue Li; Elena E. Giorgi; LaTonya D. Williams; One Dintwe; Lindsay N. Carpp; Shiyu Chen; Kelly E. Seaton; Sheetal S. Sawant; Lu Zhang; Jack Heptinstall; Shuying Liu; et al. (Emerging Microbes and Infections)
Developing an effective HIV vaccine is a momentous challenge. An exceptionally wide range of candidate HIV vaccines have been tested, yet many were poorly immunogenic, and of the select few that advanced into efficacy trials, only one demonstrated any efficacy. Here we report the results of the largest-scale cross-protocol immunogenicity comparison to date: 13 HIV vaccine trials (including 36 vaccine regimens) conducted across nine countries worldwide, strengthened by standardized trial designs, validated assays in centralized laboratories, and harmonized immunogenicity endpoints – providing an objective approach to identify the HIV vaccine candidate(s) with the best immunogenicity. A polyvalent DNA prime + protein boost regimen (HVTN 124) including Env immunogens of four subtypes, matched between prime and boost, achieved the best anti-V1V2 antibody responses by a large margin and also induced high CD4+ T-cell responses – two key immune responses implicated in HIV vaccine protection. Our results provide strong support to test this promising HIV vaccine design in more advanced phase clinical trials and will also guide the future design of additional HIV vaccines.Trial registration: ClinicalTrials.gov identifier: NCT01799954..Trial registration: ClinicalTrials.gov identifier: NCT02109354..Trial registration: ClinicalTrials.gov identifier: NCT02404311..Trial registration: ClinicalTrials.gov identifier: NCT02207920..Trial registration: ClinicalTrials.gov identifier: NCT02296541..Trial registration: ClinicalTrials.gov identifier: NCT03284710..Trial registration: ClinicalTrials.gov identifier: NCT02915016..Trial registration: ClinicalTrials.gov identifier: NCT02997969..Trial registration: ClinicalTrials.gov identifier: NCT03122223..Trial registration: ClinicalTrials.gov identifier: NCT03409276..Trial registration: ClinicalTrials.gov identifier: NCT02968849..Trial registration: ClinicalTrials.gov identifier: NCT03060629..Trial registration: ClinicalTrials.gov identifier: NCT00223080..